The "Hamopontonia corallicola" Bruce, 1970 species complex (Crustacea, Decapoda, Palaemonidae): new records and new species from the Great Barrier Reef, Australia - Marin, Ivan (Zootaxa, 2012)
The “Hamopontonia corallicola” Bruce, 1970 species complex is partly revised. The type species of the genus, H. corallicolaBruce, 1970, is redescribed based on material from Northern Australia. Additionally, two new species of the genus associatedwith hard corals are described from Lizard Island, the Great Barrier Reef, Australia. Hamopontonia fungicola sp. nov. isassociated with fungiid coral Heliofungia actiniformis (Quoy & Gaimard, 1833) and H. physogyra sp. nov. is associated withcaryophyllid coral Physogyra lichtensteini Milne-Edwards & Haime, 1851. Both species clearly differ from their congeners indistinctive coloration and morphological features. A differential key and remarks on coloration of all described species of the genus are provided.